2004
DOI: 10.1177/08830738040190020101
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Following Nonoperative Treatment of Brachial Plexus Birth Injuries

Abstract: Ninety-one infants who sustained a brachial plexus birth injury were treated with only physical and occupational therapy. The children were evaluated at 3-month intervals and followed for a minimum of 2 years. Sixty-three children with an upper or upper-middle plexus injury recovered good to excellent shoulder and hand function. In all of these children, critical marker muscles recovered M4 by 6 months of age. Twelve infants sustained a global palsy, with critical marker muscles remaining at M0-M1 at 6 months,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 14 publications
1
30
0
2
Order By: Relevance
“…10 Although true natural history studies are rare, a series by DiTaranto et al observing 63 patients without access to microsurgery reported that no child with full recovery of motor function had complete palsy and nerve root avulsion. 11 These observations are similar to those found by Eng et al 12 In patients with incomplete return of function, long-term prognosis is contingent upon neurologic recovery. Nerve root avulsions, the presence of a total plexopathy in infancy, and Horner's syndrome are poor prognostic factors.…”
Section: Natural Historysupporting
confidence: 68%
See 1 more Smart Citation
“…10 Although true natural history studies are rare, a series by DiTaranto et al observing 63 patients without access to microsurgery reported that no child with full recovery of motor function had complete palsy and nerve root avulsion. 11 These observations are similar to those found by Eng et al 12 In patients with incomplete return of function, long-term prognosis is contingent upon neurologic recovery. Nerve root avulsions, the presence of a total plexopathy in infancy, and Horner's syndrome are poor prognostic factors.…”
Section: Natural Historysupporting
confidence: 68%
“…Differences in the strength of muscles surrounding the shoulder joint can lead to soft tissue and joint contractures as well as glenohumeral joint deformity. 11,15 In addition to a better understanding of the natural history of brachial plexus injuries in terms of neurologic recovery, it is important for research to address the concerns that families and patients have regarding the appearance and limitations in daily activities resulting from the injury. Bae et al noted that upper arm, forearm, and hand lengths of the affected limbs were on average 95%, 94%, and 97%, respectively, compared with the unaffected side.…”
Section: Natural Historymentioning
confidence: 99%
“…A variety of subsequent studies, including a retrospective evaluation of 97 infants with a brachial plexus birth injury treated with only physical and occupational therapy, 4 suggest that while bicep recovery at 3 months is still a good prognostic marker, 8 the window of best opportunity for children with C5/C6±C7 injuries probably extends to at least 6 to 9 months of age, with a significant number of children showing a spontaneous recovery during the 3-to 6-month period that precludes the need for early operative intervention.…”
mentioning
confidence: 99%
“…10,21 Adult patients with brachial plexus injury are disproportionately young males, with mean ages ranging from 25 to 29 years old, who can experience major disability and a lower quality of life after injury. OBJECTIVE Pan-brachial plexus injury (PBPI), involving C5-T1, disproportionately affects young males, causing lifelong disability and decreased quality of life.…”
mentioning
confidence: 99%